2012
DOI: 10.1155/2012/838610
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Crowding: Time for Interventions and Policy Evaluations

Abstract: This paper summarises the consequences of emergency department crowding. It provides a comparison of the scales used to measure emergency department crowding. We discuss the multiple causes of crowding and present an up-to-date literature review of the interventions that reduce the adverse consequences of crowding. We consider interventions at the level of an individual hospital and a policy level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 37 publications
(31 reference statements)
1
109
0
9
Order By: Relevance
“…Several professional societies including Society of Academic Emergency Medicine (SAEM), American College of Emergency Physicians (ACEP), American Academy of Emergency Physicians (AAEM), Emergency Nurses Association (ENA), College of Emergency Medicine (CEM), Australasian College of Emergency Medicine (ACEM), Canadian Association of Emergency Physicians (CAEP), and the Institute of Medicine (IOM) have published proposals to reduce or end ED crowding [50][51][52][53][54][55][56][57]. The prospect of reducing ED crowding in the near future may be elusive, as many EDs have made major attempts for the past two decades with minimal or no improvement [58,59]. Simply building a larger ED to increase capacitance may not solve the problem, as the chief reason for overcrowding is "exit block, " or the impaired ability to move patients out of the ED [60,61].…”
Section: Solutions To Hallway Carementioning
confidence: 99%
“…Several professional societies including Society of Academic Emergency Medicine (SAEM), American College of Emergency Physicians (ACEP), American Academy of Emergency Physicians (AAEM), Emergency Nurses Association (ENA), College of Emergency Medicine (CEM), Australasian College of Emergency Medicine (ACEM), Canadian Association of Emergency Physicians (CAEP), and the Institute of Medicine (IOM) have published proposals to reduce or end ED crowding [50][51][52][53][54][55][56][57]. The prospect of reducing ED crowding in the near future may be elusive, as many EDs have made major attempts for the past two decades with minimal or no improvement [58,59]. Simply building a larger ED to increase capacitance may not solve the problem, as the chief reason for overcrowding is "exit block, " or the impaired ability to move patients out of the ED [60,61].…”
Section: Solutions To Hallway Carementioning
confidence: 99%
“…Although some wrote that shortage of hospital beds is the most prominent reason for ED overcrowding [6], we have shown that, without increasing the number of our hospital total number of beds, we managed to render our ED from crowded to non-crowded. New initiatives (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…Semakin cepat waktu pasien untuk dipindah ke ruangan semakin cepat pula waktu tunggu pasien setelah keputusan rawat inap diputuskan di IGD zona kuning. Waktu tunggu pasien setelah keputusan rawat inap diputuskan yang direkomendasikan oleh Rumah Sakit dr. Iskak Tulungagung adalah tidak lebih dari 6 jam (Boyle et al, 2012). Hal ini sesuai dengan penelitian yang dilakukan oleh Mulyono (2003) yang menyatakan bahwa proses pengambilan keputusan terkait keputusan medis di Indonesia ditentukan oleh budaya, dimana pengambil keputusan terkait tindakan medis baik dalam hal ini rawat inap adalah anggota keluarga tertua.…”
Section: Pembahasanunclassified